2016
DOI: 10.1097/grf.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Uterine Fibroids

Abstract: Uterine leiomyomata (UL) have a substantial impact on women's health, but relatively few studies have identified opportunities for primary prevention of these neoplasms. Most established risk factors are not modifiable, including premenopausal age, African ancestry, age at menarche, and childbearing history. The main challenge in studying UL is that a large proportion of tumors are asymptomatic. Herein, we review the epidemiology of UL from published studies to date. We highlight the advantages of ultrasound s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
0
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(183 citation statements)
references
References 223 publications
5
122
0
21
Order By: Relevance
“…14 A prospective cohort study was conducted by Wise LA et al, among 2146 women in US for a period of 4 years between 1997 to 2001. 14 This study showed that the women with BMI between 30.0-32.4 had highest risk of uterine fibroids. Risk was higher among parous women and weight gain since age 18 was positively associated with the risk, but only among parous women.…”
Section: Discussionmentioning
confidence: 68%
“…14 A prospective cohort study was conducted by Wise LA et al, among 2146 women in US for a period of 4 years between 1997 to 2001. 14 This study showed that the women with BMI between 30.0-32.4 had highest risk of uterine fibroids. Risk was higher among parous women and weight gain since age 18 was positively associated with the risk, but only among parous women.…”
Section: Discussionmentioning
confidence: 68%
“…These tumors are often asymptomatic and their diagnosis can be the result of an incidental finding during a gynecological exam or ultrasound check. 3 From 20% to 50% of the women with UF experience heavy menstrual bleeding and pelvic pressure; other common symptoms include infertility, increased urinary frequency or incontinence, constipation, abdominal bloating, dyspareunia, and fatigue (due to anemia from heavy bleeding). 1 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Uterine fibroids (UFs) are benign lesions and also the most common neoplasms of the female genital tract worldwide [1,2]. According to various data their prevalence may reach up to 70-80% in predisposed groups of women, but the frequency of the detection depends on selected diagnostic methods [3,4]. The risk factors for the UF's development include some modifiable and non-modifiable factors [3,5].…”
Section: Uterine Fibroids-overviewmentioning
confidence: 99%